Associate Professor Dr. Mohd Mawardi uses LEDs to develop photocatalytic reactor as source of white light (photon) - Safriza, Baharuddin (UMPSA, 2024)
PEKAN, 25 June 2024 – Researcher and lecturer of the Faculty of Electrical and Electronic Engineering Technology (FTKEE), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), Associate Professor Dr. Mohd Mawardi Saari, 37 designed a photocatalytic reactor using LEDs as a source of white light (photons).